The Typology of Partial Credit Guarantee Funds around the World - Beck, Thorsten (World Bank, Washington, DC, 2012)
This paper presents data on 76 partial credit guarantee schemes across 46 developed and developing countries. Based on theory, the authors discuss different organizational features of credit guarantee schemes and their variation across countries. They focus on the respective role of government and the private sector and different pricing and risk reduction tools and how they are correlated across countries. The findings show that government has an important role to play in funding and management, but less so in risk assessment and recovery. There is a surprisingly low use of risk-based pricing and limited use of risk management mechanisms.